The Notary's Responsibilities for the Making of Deeds and the Electronic Storage of Minutes of Deeds - Reno Reno (Sultan Agung Notary Law Review, 2022)
This study aims to determine and analyze the process and responsibilities of a notary in the manufacture and storage of minutes of deed electronically and to find out examples of deeds that contain electronic elements. The research approach method used in this thesis is a sociological juridical legal research method. This research specification uses descriptive analysis. The type of data used in this research is primary data which includes the 1945 Constitution; Act No. 2 of 2014; Code of Civil law; the Criminal Code, as well as secondary data containing books and other supporting documents. Collecting research data with interview techniques and study of documents or library materials. The data analysis method used in analyzing the data is qualitative analysis. The results showed that: First, the electronic deed has not yet obtained a strong legal basis, so it does not provide a guarantee of legal certainty. Legal certainty can be achieved, if there are no conflicting provisions between one law and another. Second, electronic storage of deed minutes can already be done because several laws already allow it. The requirement for a deed to be stored electronically is an authentic deed that must be made and stored conventionally. Storage of minutes of deeds electronically can already be done because some laws already allow it. The requirement for a deed to be stored electronically is an authentic deed that must be made and stored conventionally. Storage of minutes of deeds electronically can already be done because some laws already allow it. The requirement for a deed to be stored electronically is an authentic deed that must be made and stored conventionally.